Strengthening children’s moral development through home-based islamic religious education: A literature review on the role of muslim familie - Suresmiyati; Ida Noverta; Siti Afifatun; Farida; M. Makhrus Ali (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Children’s character development is a fundamental foundation for forming a generation that is faithful and possesses noble morals. This study aims to analyze the role of Muslim families in shaping children’s moral character through Islamic Religious Education implemented in the home environment. Employing a library research method, this study systematically reviews books, peer-reviewed journal articles, and other relevant scholarly sources that discuss family-based Islamic education and children’s moral development. The findings reveal that the family functions as the primary educational environment and serves as the first school for children. Effective moral formation is achieved through early internalization of Islamic values, particularly through parental role modeling, religious habituation, and value-based communication grounded in Islamic teachings. This study contributes to the literature by highlighting the strategic role of consistent and affectionate family-based Islamic education in fostering children’s noble character, emphasizing the importance of parental involvement in moral and religious education at home.